Length–weight relationship of six notothenioid species from sub-Antarctic waters (Beagle Channel, Argentina) - Fernandez, Daniel Alfredo; Bruno, Daniel Osvaldo; Llompart, Facundo Manuel (Journal of Applied Ichthyology)
This study presents length-weight relationships (LWR) for six species of fishes of the Suborder Notothenioidei that inhabit the sub-Antarctic waters of the Beagle Channel (Argentina). These species represent five of the nine families of this Suborder. The specimens belong to historical fish collections in the area (from 1987 to 1990) using gill and trammel nets. All species but Eleginops maclovinus had no previous LWR estimates. The coefficient of determination (r 2 ) ranged from 0.91 to 0.99 and b values ranged from 2.74 to 3.2. Harpagifer bispinis was the only species with a b value lower than three. This information is useful to predict the weight from the length data and to provide insights into the ecology of sub-Antarctic nototheniod fish. Fil: Fernandez, Daniel Alfredo. Universidad Nacional de Tierra del Fuego. Instituto de Ciencias Polares, Recursos Naturales y Ambiente; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Bruno, Daniel Osvaldo. Universidad Nacional de Tierra del Fuego. Instituto de Ciencias Polares, Recursos Naturales y Ambiente; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Llompart, Facundo Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego. Instituto de Ciencias Polares, Recursos Naturales y Ambiente; Argentina